Atypical protein kinase C-ζ modulates clonogenicity, motility, and secretion of proteolytic enzymes in murine mammary cells - Urtreger, Alejandro Jorge (2005)
In this paper, we investigated whether protein kinase C-ζ (PKCζ), a member of the atypical PKC family, induces phenotypic alterations associated with malignant transformation and tumor progression in mammary cells. The stable overexpression of PKCζ in immortalized mammary epithelial cells (NMuMG), activates the mitogenic extracellular signal-regulated kinase (ERK) pathway, enhanced clonal cell growth and exerts profound effects on proteases secretion. The effect on proteases expression seems to be specific for urokinase-type plasminogen activator and metalloproteinase-9 (MMP-9) because no modulation in MMP-2 and MMP-3 production could be detected. In addition, our experiments demonstrated that PKCζ overexpression markedly altered the adhesive, spreading, and migratory abilities of NMuMG cells. The overexpression of this enzyme was not sufficient to confer an ancho rage-independent growth capacity. An extensive mutational analysis of PKCζ revealed that the effects observed in NMuMG cells were strictly dependent on the kinase (catalytic) domain of the enzyme. Taken together, these results suggest that in mammary cells PKCζ modulates several of the critical events involved in tumor development and dissemination through the activation of mitogen activated protein kinase (MAPK)XERK pathway.